2014
DOI: 10.12659/msm.890635
|View full text |Cite
|
Sign up to set email alerts
|

Novel fibro-inflammation markers in assessing left atrial remodeling in non-valvular atrial fibrillation

Abstract: BackgroundStructural remodeling is associated with the fibroinflammatory process in the atrial extracellular matrix. In the present study we aimed to investigate whether serum levels of new circulating remodeling markers differ in patients with atrial fibrillation (AF) compared to patients with sinus rhythm.Material/MethodsThe study population included 52 patients diagnosed with non-valvular AF and 33 age-matched patients with sinus rhythm. Serum levels of Galectin-3, matrix metalloproteinase-9 (MMP-9), lipoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 38 publications
1
38
1
1
Order By: Relevance
“…Galectin-3 has been associated with atrial remodeling in AF patients 9 , with AF recurrence in patients who have undergone ablation, 11 with cardiometabolic disease 26 , and with AF prevalence in case-control studies. 9,27,28 On the other hand, 2 prior prospective epidemiological studies failed to find an independent association between galectin-3 levels and the incidence of AF. 12,15 In both studies, higher galectin-3 concentrations were associated with an increased risk of AF in individuals in unadjusted analyses, but not after adjustment for other AF risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin-3 has been associated with atrial remodeling in AF patients 9 , with AF recurrence in patients who have undergone ablation, 11 with cardiometabolic disease 26 , and with AF prevalence in case-control studies. 9,27,28 On the other hand, 2 prior prospective epidemiological studies failed to find an independent association between galectin-3 levels and the incidence of AF. 12,15 In both studies, higher galectin-3 concentrations were associated with an increased risk of AF in individuals in unadjusted analyses, but not after adjustment for other AF risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…7 Inhibition of galectin-3 has been shown to interfere with myocardial fibrogenesis, and some have suggested it might be a therapeutic target for AF. 8 Galectin-3 has been associated with atrial remodeling in AF patients 9 and outcomes after catheter ablation of atrial AF. 10,11 Recent epidemiologic studies have shown that blood levels of galectin-3 are associated positively with incident heart failure (HF) and coronary heart disease (CHD), 6,1214 but to our knowledge, only 2 prospective studies of exclusively whites have tested whether galectin-3 concentrations are associated with incident AF.…”
mentioning
confidence: 99%
“…41 Serum levels of the fibro-inflammatory biomarkers MMP-9, type III procollagen, and hs-CRP, were greater in persistent-AF patients than in SR controls, and positively correlated with echocardiographic left atrial volume, an index of atrial remodeling. 42 After AF ablation, serum levels of some fibro-inflammatory biomarkers (hs-CRP and IL-6) decreased in patients without AF recurrence, whereas others (tissue inhibitor of metalloproteinase-2 (TIMP-2), matrix metalloproteinase-2 (MMP-2), carboxyl-terminal telopeptide of collagen type I) increased. 43 Baseline MMP-2 levels were greater in those with recurrence.…”
Section: Inflammation and Fibrosis In Afmentioning
confidence: 99%
“…However, to date, the exact relation between the extent and severity of low‐voltage regions and the degree of LA fibrosis/remodelling needs further clarification. Biomarkers have been used as a surrogate for atrial remodelling, reflecting mechanical stress, fibrosis, or inflammation; but individual markers to date lack atrial specificity 13, 14, 15…”
Section: Clinical Diagnosis Of Atrial Remodellingmentioning
confidence: 99%